The Prevalence and Causes of Non-adherence to Immunosuppressive Medications in Patients with Lupus Nephritis Flares - Ali, Ahmed Y.; Abdelaziz, Tarek Samy; Behiry, Mervat Essam (Current Rheumatology Reviews, 2020)
Background: Lupus nephritis is one of the major manifestations of SLE. Poor adherence to medications is an important cause of not achieving treatment targets. Methods: We assessed patients’ adherence to immune-suppressive medications in patients with Lupus nephritis using the Morisky, Green, and Levine (MGL) Adherence Scale. The aim was to study the effect of non-adherence on the occurrence of renal flares. Results: We recruited 104 patients with lupus nephritis. Sixty-six patients had flares of LN. There was a high prevalence of non-adherence to medications (n=68). Patients who were non-adherent to treatment had more renal flares (p= 0.02). Duration of lupus since diagnosis was significantly higher in patients who had renal flares. Using regression analysis, non-adherence to medications was associated with 3.7 higher risk of developing a single renal flare and 4.9 higher risk of developing more than one renal flare. Causes of non-adherence were medications side effects in 43% of patients, financial issues in 31% or forgetfulness in 26%. Conclusion: Non-adherence to immunosuppressive medications has a high prevalence in patients with lupus nephritis and is correlated with the number of renal flares.
Keywords: medication